A cidade (in) visível no quarto distrito de Porto Alegre : a retórica em torno da participação cidadã no programa +4D de regeneração urbano - Cortez, Shirlei Debastiani (2022)
This research deals with citizen participation in the +4D Urban Regeneration Program of the 4th District of Porto Alegre. The Program proposed by the government has the following strategic axes: infrastructure, social and economic development, urban and cultural rehabilitation, under the prism of sustainable urban development. The general objective of this research was to understand how community leaders and representatives perceive citizen participation in the +4D Urban Regeneration Program of the 4th District of Porto Alegre. For this purpose, a qualitative and exploratory methodology was used, with interpretive epistemology and an inductive approach, through 15 in-depth interviews and secondary data collection, using thematic analysis to categorize and interpret the data. The results of this research point to an emptying of the participatory process through the limitation of citizens' access and of the exclusion of citizenship (communities directly affected by the +4D Program) that were not invited to the discussion and through false listening to representatives of society civil society, demonstrating the lack of transparency in the actions of the public power. What was found was the rhetoric of citizen participation in the speech of policy makers. These results are associated with the model of hegemonic democracy, where representation prevails over participation, distancing the citizen from decision-making. Even mechanisms such as social control and transparency that are labeled as citizen participation in hegemonic democracies suggest the exhaustion of the representative model. Hence the need for real mechanisms that guarantee the broad participation of citizenship. In view of the themes that emerged from the field, it was possible to understand how leaders and community representatives perceived citizen participation in the +4D Program, both the place of non-citizen participation, and the understanding of how the Program was debated in the CMDUA and the consequent process of false listening in this representative space. In addition, the +4D Program was identified, as a smart city initiative, it did not effectively integrate citizens, especially communities in situations of social vulnerability and recyclers in the region. In other words, the (in)visible city of the fourth district is visible to the eyes of those who enter and leave the city of Porto Alegre through the Humaitá region, but invisible to the eyes of the municipal public authorities. In practice, what was found in the +4D Program was a neoliberal logic focused on the market, where the solution for the fourth district involves large enterprises and urban regeneration. The different ways of living in this territory were disregarded. The contribution of this work was to discuss citizen participation from the counter-hegemonic conception of democracy, which places the citizen as the protagonist of the democratic process. In view of this, it becomes urgent, from the field of Public Administration, to rethink and discuss truly participatory methodologies for public management and that include the citizen in decision-making and that these decisions become binding.